Growth Assessment of Tropical Sugarbeet as Influenced by Spacing (Bangladesh Agronomy Journal, 2021)
The experiment was carried out at the research field of Agronomy and Farming Systems Division, Bangladesh Sugarcrop Research Institute (BSRI), Ishurdi, Pabna during 2012-2013 to determine the most suitable spacing for sugarbeet cultivation in Bangladesh. The experiment was conducted with nine spacing viz. 50 cm × 20 cm, 60 cm × 20 cm, 70 cm × 20 cm, 50 cm × 25 cm, 60 cm × 25 cm, 70 cm × 25 cm, 50 cm × 30 cm, 60 cm × 30 cm and 70 cm × 30 cm in a randomized complete block design with three replications. The effects of spacing on sugarbeet plantation were observed on growth and growth contributing components (germination percentage, number of leaves plant-1, root length, shoot length, root fresh weight, shoot fresh weight, root dry weight, shoot dry weight, crop growth rate) of sugarbeet. The highest germination percentage (95.67%), number of leaves plant-1 (34.33) at 30 DAS, shoot length (54.07 cm) at 120 DAS, root fresh weight (969.47 g plant-1) at 150 DAS, shoot fresh weight (752.47 g plant-1) at 120 DAS and other growth contributing parameters were obtained with the spacing 70 cm × 30 cm. However, the maximum root length (38.97 cm) was obtained with 50 cm × 20 cm spacing. It was concluded that the wider spacing promoted the growth of individual beet, though the optimum spacing for maximum root growth of sugarbeet was 50 cm × 20 cm.Bangladesh Agron. J. 2020, 23(2): 51-58